The Rich Solid-State Phase Behavior of dl-Aminoheptanoic Acid: Five Polymorphic Forms and Their Phase Transitions - Smets, Mireille M. H. (Cryst Growth Des, 2017)
[Image: see text] The rich landscape of enantiotropically related polymorphic forms and their solid-state phase transitions of dl-2-aminoheptanoic acid (dl-AHE) has been explored using a range of complementary characterization techniques, and is largely exemplary of the polymorphic behavior of linear aliphatic amino acids. As many as five new polymorphic forms were found, connected by four fully reversible solid-state phase transitions. Two low temperature forms were refined in a high Z′ crystal structure, which is a new phenomenon for linear aliphatic amino acids. All five structures consist of two-dimensional hydrogen-bonded bilayers interconnected by weak van der Waals interactions. The single-crystal-to-single-crystal phase transitions involve shifts of bilayers and/or conformational changes in the aliphatic chain. Compared to two similar phase transitions of the related amino acid dl-norleucine, the enthalpies of transition and NMR chemical shift differences are notably smaller in dl-aminoheptanoic acid. This is explained to be a result of both the nature of the conformational changes and the increased chain length, weakening the interactions between the bilayers.